Functional comparison of the endothelial nitric oxide synthase Glu298Asp polymorphic variants in human endothelial cells. - McDonald, D; Alp, N; Channon, K (2004)
The G894T endothelial nitric oxide synthase (eNOS) polymorphism results in a Glu to Asp substitution at position 298. This position is located externally on the protein and as the regulation of eNOS is dependent on its subcellular localization and interaction with modulatory proteins, we aimed to address whether the substitution of Asp at 298 had any effect on these mechanisms. Initially, we developed a novel method to accurately determine molar quantities of each variant by expressing them as green fluorescent protein (GFP) fusion proteins and using recombinant adenoviruses to facilitate transient infection of human microvascular endothelial cells. Sodium dodecyl sulphate-polyacrylamide gel electrophoresis and Western blotting of eNOSAsp revealed a 135-kDa proteolytic fragment which was not present with eNOSGlu. This proteolysis was prevented by using LDS buffer confirming that this differential cleavage is an artefact of sample preparation and unlikely to occur intracellularly. Nitric oxide was measured following stimulation with calcium ionophore or oestrogen in the presence of varying sepiapterin concentrations. GFP fluorescence was used to quantify the amount of fusion protein and calculate intracellular specific activity. There was no significant difference in intracellular specific activity between Glu and Asp eNOS in response to calcium ionophore or oestrogen. Tetrahydrobiopterin supplementation increased eNOS activity of both variants in an identical manner. The presence of the GFP also facilitated the visualization of the variants by confocal microscopy and demonstrated that both localized to the plasma membrane and the Golgi. These findings demonstrate that the Asp substitution at 298 does not have a major effect in modulating eNOS activity in vivo.